Clinical Correlates of Childhood Trauma and Dissociative Phenomena in Patients with Severe Psychiatric Disorders - YANARTAŞ, ÖMER (SPRINGER, 2014)
In this present study, we aim to investigate the possibility of a link between psychotic disorders and traumatic experiences in a group of female patients diagnosed with psychotic disorders by comparing childhood trauma exposure with a group of non-psychotic psychiatric disorder attending the same pschiatric clinic. Secondary purpose of this study is to examine the clinical correlates of trauma exposure, dissociative phenomena and psychiatric symptomatology between these two group of patients. Two psychiatric sample groups, those with psychotic disorders-mostly schizophrenic-(n = 54), and those with a non-psychotic severe psychiatric disorders (n = 24), were recruited. Data were collected for demographic, psychiatric and trauma histories and psychiatric symptomatology for all patients. In this study, high prevalance rates of childhood traumatic experiences and dissociative phenomena were found in both groups. Total scores of childhood trauma questionnaire in favor of the non-psychotic group were found to be close to significance (p = 0.052). DES scores of non-psychotic group were also higher although not statistically significant. 54.2 % of nonpsychotic cases had DES scores > 20 on the other hand, that percentage of psychotic cases were found to be as 38.9 %. Furthermore, psychiatric patients who have suffered childhood traumatic experiences are far more likely to try to kill themselves than psychiatric patients who have not experienced such abuse. The high rates of childhood traumatic events in our present samples of both schizophrenia-spectrum patients and nonpsychotic patients confirm the need for clinicans to take trauma histories routinely.
Keywords: Childhood trauma; Dissociation; Psychosis; Nonpsychotic psychiatric disorders; SEXUAL-ABUSE; FEMALE-PATIENTS; SCHIZOPHRENIA; PSYCHOSIS; SYMPTOMS; PSYCHOPATHOLOGY; HALLUCINATIONS; INPATIENTS; HISTORY; MODEL